The Queen's Royal College, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Wilson and Johnstone, Trinidad, 2010)
Exterior view of the front of the Queen’s Royal College (QRC), Maraval Road, Queen's Park West, Port of Spain, Trinidad. One of the main government secondary schools for boys in Port of Spain, it was designed by Daniel M. Hahn, qualified architect and past student of QRC, and opened here 25 March, 1904, on lands that were once part of the government farm, St. Clair. Postcard number J286.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; [1930]; Cities and towns--Trinidad and Tobago--Port of Spain; Historic buildings--Trinidad and Tobago; Schools--Trinidad and Tobago; High schools--Trinidad and Tobago; Public schools--Trinidad and Tobago; Education, Secondary--Trinidad and Tobago; Architecture--Trinidad and Tobago; Architecture--Details; Towers--Trinidad and Tobago; Tower clocks--Trinidad and Tobago; Clocks and watches--Trinidad and Tobago; Windows--Trinidad and Tobago; Fences--Trinidad and Tobago; Palms--Trinidad and Tobago; Shrubs--Trinidad and Tobago; Roads--Trinidad and Tobago; Electric lines--Trinidad and Tobago; Overhead electric lines--Trinidad and Tobago; Magnificent Seven, The (Port of Spain); Queen's Park Savannah (Port of Spain); Queen's Royal College (Trinidad and Tobago)